Prevalence and molecular characterization of human noroviruses and sapoviruses in Ethiopia - Sisay, Z.; Djikeng, Appolinaire; Berhe, N.; Belay, G.; Gebreyes, W.; Abegaz, W.E.; Njahira, Moses N.; Wang, Q.H.; Saif, L.J. (Springer, 2016)
Viral gastroenteritis is a major public health problem worldwide. In Ethiopia, very limited studies have been done on the epidemiology of enteropathogenic viruses. The aim of this study was to detect and characterize noroviruses (NoVs) and sapoviruses (SaVs) from acute gastroenteritis patients of all ages. Fecal samples were collected from diarrheic patients (n = 213) in five different health centers in Addis Ababa during June-September 2013. The samples were screened for caliciviruses by reverse transcription polymerase chain reaction (RT-PCR) using universal and genogroup-specific primer pairs. Phylogenetic analyses were conducted using the sequences of the PCR products. Of the clinical samples, 25.3 % and 4.2 % were positive for NoV and SaV RNA, respectively. Among the norovirus positives, 22 were sequenced further, and diverse norovirus strains were identified: GI (n = 4), GII (n = 17) and GIV (n = 1). Most strains were GII (n = 17/22: 77.2 %), which were further divided into three different genotypes (GII.4, GII.12/GII.g recombinant-like and GII.17), with GII.17 being the dominant (7/17) strain detected. GI noroviruses, in particular GI.4 (n = 1), GI.5 (n = 2) and GI.8 (n = 1), were also detected and characterized. The GIV strain detected is the first from East Africa. The sapoviruses sequenced were also the first reported from Ethiopia. Collectively, this study showed the high burden and diversity of noroviruses and circulation of sapoviruses in diarrheic patients in Ethiopia. Continued surveillance to assess their association with diarrhea is needed to define their epidemiology, disease burden, and impact on public health.